Mixture toxicities of tetrachlorantraniliprole and tebuconazole to honey bees (Apis mellifera L.) and the potential mechanism. (February 2023) - Cang, Tao; Lou, Yancen; Zhu, Yu-Cheng; Li, Wenhong; Weng, Hongbiao; Lv, Lu; Wang, Yanhua
Graphical abstract: Highlights: Tetrachlorantraniliprole had a higher toxicity to the honey bees than tebuconazole. Tetrachlorantraniliprole when mixed with tebuconazole caused synergistic toxicity. Expression levels of 5 genes in mixtures exerted greater changes than individuals. Synergistic effects should be considered into risk evaluation of pesticide mixture. Abstract: The extensive use of pesticides has negative effects on the health of insect pollinators. Although pollinators in the field are seldom exposed to individual pesticides, few reports have assessed the toxic impacts of pesticide combinations on them. In this work, we purposed to reveal the combined impacts of tetrachlorantraniliprole (TET) and tebuconazole (TEB) on honey bees (Apis mellifera L.). Our data exhibited that TET had greater toxicity to A. mellifera (96-h LC50 value of 298.2 mg a.i. L -1 ) than TEB (96-h LC50 value of 1, 841 mg a.i. L -1 ). The mixture of TET and TEB displayed acute synergistic toxicity to the pollinators. Meanwhile, the activities of CarE, CYP450, trypsin, and sucrase, as well as the expressions of five genes ( ppo, abaecin, cat, CYP4G11, and CYP6AS14 ) associated with immune response, oxidative stress, and detoxification metabolism, were conspicuously altered when exposed to the mixture relative to the individual exposures. These results provided an overall comprehension of honey bees upon the challenge of sublethal toxicity between neonicotinoid insecticides and triazole fungicides and could be used to assess the intricate toxic mechanisms in honey bees when exposed to pesticide mixtures. Additionally, these results might guide pesticide regulation strategies to enhance the honey bee populations.